2010
DOI: 10.1111/j.1399-6576.2010.02248.x
|View full text |Cite
|
Sign up to set email alerts
|

Induced hypothermia in comatose survivors of asphyxia: a case series of 14 consecutive cases

Abstract: The results of this study suggest that an early abnormal CT scan of the brain in patients resuscitated after asphyxiation carries an adverse prognosis. The favorable outcome of the patients in the present study suggests that a randomized clinical trial on the use of induced hypothermia in patients exposed to severe asphyxia might be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Similar experience has been reported in patients with asphyxia-associated cardiac arrest from hanging and non-fatal drowning, who were treated with therapeutic hypothermia. 14,15 In our sample, ALS administered by an emergency physician did not improve outcome if bystander CPR did not previously restore spontaneous circulation, although ROSC has been observed in some victims after epinephrine administration.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Similar experience has been reported in patients with asphyxia-associated cardiac arrest from hanging and non-fatal drowning, who were treated with therapeutic hypothermia. 14,15 In our sample, ALS administered by an emergency physician did not improve outcome if bystander CPR did not previously restore spontaneous circulation, although ROSC has been observed in some victims after epinephrine administration.…”
Section: Discussionmentioning
confidence: 82%
“…In more than half of all avalanche victims with ROSC severe cerebral injury was already indicated by significant cerebral oedema seen in a CT scan at hospital admission. Cerebral oedema is a known poor prognostic sign for patients resuscitated after asphyxia, 15 and a CT scan on hospital arrival may be helpful in identifying avalanche victims with a particularly dismal prognosis very early.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have suggested that unconscious near-hanging patients resuscitated from cardiac arrest should be considered for TH 4 12. In a study by Borgquist and Friberg that included three patients resuscitated from asphyxial cardiac arrest after near-hanging, all three patients were treated with TH, and only one patient survived with complete neurological recovery 4.…”
Section: Discussionmentioning
confidence: 99%
“…There are small case series and case reports describing variable neurological outcomes when TTM was used after cardiac arrest associated with various etiologies [25][26][27][28][29][30][31][32][33][34][35][36][37][38] . A case series of 14 consecutive comatose survivors of asphyxia that were treated with TTM observed a survival rate of 65% 25 . In another retrospective cohort study of 16 unconscious patients after near hanging, 13 patients received TTM and 12 of them had poor neurological outcomes 38 .…”
Section: Quality Of Evidence: Low Strength Of Recommendation: Conditimentioning
confidence: 99%